Pengaruh Harga, Kualitas Produk, Citra Merek dan Sertifikasi Halal terhadap Minat Beli Mahasiswa pada Produk Almaz Fried Chicken: Studi Kasus pada Almaz Fried Chicken Condet - Saddam Al Imroni; Shoimatul Fitria (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the influence of price, food quality, halal certification, and brand image on the purchase intention of Almaz Fried Chicken among university students in Jakarta. A quantitative approach was employed using a survey method, with multiple linear regression analysis as the primary analytical technique. The population consisted of active university students in Jakarta, and a sample of 108 respondents was selected through purposive sampling. Data were collected using a structured questionnaire based on a 6-point Likert scale. The results indicate that price, food quality, halal certification, and brand image each have a positive and significant effect on purchase intention. Simultaneously, these four variables also significantly influence students’ purchase intention toward Almaz Fried Chicken Condet. These findings highlight the potential for local brands to compete in the fast food market through effective management of pricing, product quality, halal assurance, and brand perception.